Exercises for wrist flexibility, arm power, concentration and shooting results on petanque - Irhas Syahwira; Said Junaidi; Taufiq Hidayah; Sri Sumartiningsih; Setya Rahayiu (JUARA : Jurnal Olahraga, 2022)
The aims of this study were: 1) To analyze the effect of wrist flexibility exercise on shooting results; 2) To analyze the impact of arm power training on shooting results; 3) To investigate the effect of concentration training on shooting results; 4) To examine the impact of wrist flexibility exercise, arm power and exercise. Concentration on the results of shooting petanque. This study uses a pre-experimental method with the "One Group Pretest Posttest Design" research design. The instrument used to test the shooting ability is the number game shooting station 1, 2, 3, 4, and 5 with a distance of 6 meters. The subjects in this study were petanque athletes in Indragiri Hulu Regency, totalling 18 sons, using purposive sampling. The results of this study: 1) There is an effect of wrist flexibility exercises on the results of shooting petanque. 2) There is an effect of arm power training on the results of shooting petanque. 3) There is an effect of concentration training on the results of shooting petanque. 4) There are similarities between the results of wrist flexibility exercises, arm power, and concentration and without concentration on the shooting results of petanque athletes in the Indragiti upstream district. Based on the results of the study, it can be concluded that there is a significant effect between wrist flexibility, arm power, and concentration on shooting results in petanque athletes in Indragiri Hulu Regency, based on the T-test simultaneously. This means that Wrist Flexibility, Arm Power, and Concentration are very influential in petanque sports.